Trust in management, change resistance and work engagement on startup employees in Indonesia - Aziza, Dhimas Fachri; Nadia, Fiona Niska Dinda (Jurnal Ilmiah Psikologi Terapan, 2023)
Dynamic industrial development requires many organizations to have the right competitive business strategy. Indonesian startups are no exception. Startups must think about ways to develop their human resources. In addition, because startups are companies that have just grown, startup owners need to build trust in their members to achieve what is planned according to the company’s targets. This study will examine the role of trust in management on work engagement among startup employees in Indonesia, focusing on mediating change resistance. The participants actively involved in this study were 100 start-up members at the staff to middle manager level and were selected based on a purposive sampling technique. The instruments used are the change resistance scale, the trust in management scale, and the work engagement scale. The PLS-SEM method test results found a significant positive role for trust in management on work engagement; trust in management affects change resistance, and change resistance affects work engagement. This means that trust in management can further strengthen its role in increasing work engagement if it is mediated by change resistance.